2011
DOI: 10.1103/physrevlett.106.216803
|View full text |Cite
|
Sign up to set email alerts
|

Direct Measurement of the Out-of-Plane Spin Texture in the Dirac-Cone Surface State of a Topological Insulator

Abstract: We have performed spin-and angle-resolved photoemission spectroscopy of Bi2Te3 and present the first direct evidence for the existence of the out-of-plane spin component on the surface state of a topological insulator. We found that the magnitude of the out-of-plane spin polarization on a hexagonally deformed Fermi surface of Bi2Te3 reaches maximally 25% of the in-plane counterpart while such a sizable out-of-plane spin component does not exist in the more circular Fermi surface of TlBiSe2, indicating that the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
151
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 203 publications
(162 citation statements)
references
References 26 publications
11
151
0
Order By: Relevance
“…The reason is hexagonal warping [24] near the Fermi surface [see the top of Fig. 2(i)] that is rather small in Bi 2 Se 3 as compared to Bi 2 Te 3 [8].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reason is hexagonal warping [24] near the Fermi surface [see the top of Fig. 2(i)] that is rather small in Bi 2 Se 3 as compared to Bi 2 Te 3 [8].…”
Section: Resultsmentioning
confidence: 99%
“…Understanding and utilization of the spin properties of TI materials are believed to be the key to measuring the topological invariances hidden in the bulk electronic wave functions [2] and realizing exotic magnetic-spin physics such as the axion electrodynamics [3,4] or the magnetic monopole [5], as well as future spin-based low-power transistors and devices. While extensive SR-ARPES studies on various TI compounds have successfully identified and confirmed the helical spin texture of the TSSs [6][7][8][9][10], much remains to be addressed regarding the critical response of the measured spin properties to the incident light and its polarizations (electric or magnetic fields).…”
Section: Introductionmentioning
confidence: 99%
“…98) Intriguingly, this hexagonal warping gives rise to peculiar physics such as strong quasiparticle interference 99,100) and appearance of a finite out-of-plane spin polarization. 101) While Bi 2 Se 3 and Bi 2 Te 3 are conceptually simple TI materials, their chemistry is not so simple and they are always degenerately doped due to naturally occurring crystalline defects, which cause their transport properties to be dominated by bulk carriers. In this respect, a promising TI material having the tetradymite structure is Bi 2 Te 2 Se, which has a chalcogen-ordered structure shown in Fig.…”
Section: Three-dimensional Tismentioning
confidence: 99%
“…The surface states of these topological insulators are spin polarized and protected by time-reversal symmetry. A number of surface spectroscopy measurements, such as spin and angle-resolved photoemission spectroscopy (ARPES) [5][6][7][8][9][10][11][12][13] and scanning tunneling microscopy 14,15 , have been used to detect the topologically nontrivial surface state in three-dimensional topological insulator Bi 1-x Sb x , Bi 2 Se 3 , Bi 2 Te 3 , etc. The exotic surface states of topological insulators are expected to form a playground of various topological quantum effects and show great potential in spintronics and quantum computation [16][17][18] .…”
mentioning
confidence: 99%